Ablation of cardiac arrhythmias using a three-dimensional electro-anatomical mapping system in the Instituto Nacional Cardiovascular - INCOR - Soto-Becerra, Richard (2021)
Objective. To describe the initial experience in ablation of cardiac arrhythmias using 3D mapping at the Instituto Nacional Cardiovascular INCOR (Lima, Peru). Methods. A retrospective descriptive study was carried out. During February 2020, data was collected from the medical records of all patients in whom ablation was performed using 3D mapping from July 2017 to December 2019. This procedure was performed in patients with symptomatic arrhythmia refractory to antiarrhythmic therapy. Results. Data were collected from 123 patients (median age: 46 years, 64.2% male), who had a median time of illness of 6 years. Among the arrhythmias treated, 19% had atrial fibrillation, 17.5% atrial tachycardia, 17.5% idiopathic ventricular arrhythmias, 16.6% Wolf Parkinson White syndrome / Atrioventricular reentrant tachycardia, 11.1% ventricular arrhythmias of the His-Purkinje conduction system, 9.5% scar related ventricular tachycardia associated, 6.4% atrial flutter and 2.4% intranodal tachycardia. The median fluoroscopy time was 26 minutes. Ablation was acutely successful in 95.9% of cases, acute complications were observed in 4.8%, and recurrence-free survival during the first year of follow-up was 74%. Conclusions. Our experience in ablation of cardiac arrhythmias using 3D mapping had a high acute success rate, low frequency of complications, and one-year recurrence-free survival of 74%.